Media worlds : anthropology on new terrain - Ginsburg, Faye D.; Abu-Lughod, Lila.; Larkin, Brian (Berkeley : University of California Press, 2002)
This groundbreaking volume showcases the exciting work emerging from the ethnography of media, a burgeoning new area in anthropology that expands both social theory and ethnographic fieldwork to examine the way media--film, television, video--are used in societies around the globe, often in places that have been off the map of conventional media studies.
Screen memories: resignifying the traditional in indigenous media / Faye D. Ginsburg -- Visual media and the primitivist perplex: colonial fantasies, indigenous imagination, and advocacy in North America / Harald E.L. Prins -- Representation, politics, and cultural imagination in indigenous video: general points and Kayapo examples / Terence Turner -- Spectacles of difference: cultural activism and the mass mediation of Tibet / Meg McLagan -- Egyptian melodrama: technology of the modern subject? / Lila Abu-Lughod -- Epic contests: television and religious identity in India / Purnima Mankekar -- The national picture: Thai media and cultural identity / Annette Hamilton -- Television, time, and the national imaginary in Belize / Richard R. Wilk -- Mass media and transnational subjectivity in Shanghai: notes on (re)cosmopolitanism in a Chinese metropolis / Mayfair Mei-hui Yang -- A Marshall plan of the mind: the political economy of a Kazakh soap opera / Ruth Mandel -- Mapping Hmong media in diasporic space / Louisa Schein -- Putting American public television documentary in its places / Barry Dornfeld -- Culture in the ad world: producing the Latin look / Arlene Dávila -- "And yet my heart is still Indian": the Bombay film industry and the (h)Indianization of Hollywood / Tejaswini Ganti -- Arrival scenes: complicity and media ethnography in the Bolivian public sphere / Jeff D. Himpele -- The materiality of cinema theaters in northern Nigeria / Brian Larkin -- Mobile machines and fluid audiences: rethinking reception through Zambian radio culture / Debra Spitulnik -- The Indian work of art in the age of mechanical reproduction: or, what happens when peasants "get hold" of images / Christopher Pinney -- Live or dead? Televising theater in Bali / Mark Hobart -- A room with a voice: mediation and mediumship in Thailand's information age / Rosalind C. Morris.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Mass media and culture; Médias et culture; SOCIAL SCIENCE -- Media Studies; SOCIAL SCIENCE -- Anthropology -- General; Mass media and culture; Massenmedien; Anthropologie; USA; Massamedia; Culturele antropologie; anthropologists; anthropology; cross cultural; cultural history; cultural studies; ethnographic; ethnographics; ethnography; film history; film studies; global; international; media history; media studies; media; multimedia; pop culture; social history; social studies; television history; television; theoretical; transnational; Electronic book